PENGARUH EFISIENSI BIAYA BANTUAN OPERASIONAL SEKOLAH (BOS) TERHADAP PENINGKATAN KUALITAS PENDIDIKAN DI UPT SD NEGERI 065006 BELAWAN - Indri Cendana Br. Sitanggang; Dewi Wahyuni (UNIVERSITAS DHARMAWANGSA, 2022)
Education is a right for all people. In its implementation, education costs are needed which are obtained from the cost of school operational assistance (BOS). Education costs are all types of expenditures related to the implementation of education, both in the form of money and goods and labor that can be valued for money. Cost is a potential that greatly determines the quality of education, because it is very important, it is necessary to manage costs effectively and efficiently in order to produce quality schools and have quality students. In improving the quality of education, strong support is needed in the activities of the learning process, the use of educational facilities and infrastructure in accordance with the provisions of national education standards. In this study, the authors examine the realization of the use of BOS funds and the responses of students about the use of BOS funds at UPT SD Negeri 065006 Belawan. School operational assistance is assistance from the government to schools based on the number of students in the school. The amount of costs includes the cost of providing facilities and infrastructure, developing human resources, and working capital. The BOS fee is expected to ease the burden on parents for their children's education. Quality education is education that is able to carry out the process of quality education by freeing students from ignorance, incompetence, powerlessness, untruth, dishonesty, and from bad morals and faith. If the BOS funds are used properly, it will certainly produce quality students. The research method used is quantitative with a simple linear regression analysis approach, validity test, and reliability test. The population in this study was the principal, all people who were in UPT SD Negeri 065006 Belawan. The samples in this study were principals, teachers, and fifth and sixth grade students. Sources of data collection used in this study were interview, observation, documentation, and questionnaire techniques.